Bioaccumulation and trophic transfer of organophosphate esters in tropical marine food web, South China Sea - Ding, Yang; Han, Minwei; Wu, Zhiqiang; Zhang, Ruijie; Li, An; Yu, Kefu; Wang, Yinghui; Huang, Wen; Zheng, Xiaobo; Mai, Bixian (Environment international, 2020)
[Display omitted] •Ten OPEs were detected in organisms of a coral reef foodweb in the South China Sea.•Composition profiles of OPEs were species-specific among different organisms.•Biomagnification of TPTP in the pelagic foodweb was found for the first time.•A significantly linear correlation was found between TMFs and latitudes. Environmental exposure to organophosphate esters (OPEs) continues to be a concern. Little is known about their bioaccumulation and trophodynamics, especially in tropical food webs. This study collected seawater and fifteen types of organism from a tropical ecosystem, South China Sea, to investigate the species-specific compositional, bioaccumulation, and trophic transfer of OPEs. The total concentrations of 11 target OPEs (ng/g dw) in the organisms decreased with the increase of their trophic levels in the order: phytoplankton (922) > zooplankton (660) > oysters (309) > crabs (225) > coral tissues (202) > fishes (58.2). The composition profiles (relative abundances) of OPEs were different among the species of organisms, which is likely affected by metabolism and the physicochemical property of OPEs. The trophic biomagnification of tripentyl phosphate (TPTP) in the pelagic food web was unexpected and requires further investigation. The trophic magnification factors (TMFs) of OPEs were generally lower in this tropical aquatic food web than in temperate and frigid aquatic food web. Our analysis suggests that there is a significant positive linear correlation between latitude and TMF. Intakes of OPEs through the consumption of the seafood involved in this work does not pose health risk to adults.